STUDI DESKRIPTIF PENGELOLAAN PENDIDIKAN INKLUSIF DI SEKOLAH DASAR - Indrian Prasanti, Mauli (Jurnal Pendidikan Khusus, 2017)
Abstract : The purpose of this study is to obtain a picture of student management, curriculum management, management of teachers and education personnel, and management of facilities and infrastructure in inclusive education. The research method used is descriptive qualitative. Data collection methods used were interviews, observation and documentation. Data analysis techniques used include data reduction, data display, and data verification / draw conclusions. The results of this study can be concluded (1) the management of students in SDN Lemahputro 1 is good enough that includes the process of acceptance of learners (including the results of IQ test and audiology test results), and the process of identifying and assessing the implementation after the prospective learners have started the process of teaching and learning At school, (2) curriculum management at SDN Lemahputro 1 Sidoarjo that develops modification curriculum, implementation of PPI and special program for learners; (3) management of educator and educational staff at SDN Lemahputro 1 which includes the existence of classroom teachers and special teachers GPK for participants Students with special needs, priority of experience, (4) management of facilities and infrastructure covering public facilities and special facilities where there are procurement tools, media procurement and secure accessibility for learners with special needs.   Keywords: Management, Inclusive Education